KEHIDUPAN SOSIAL EKONOMI BURUH PENGGALI PASIR DI KECAMATAN SUNGAI RUMBAI KABUPATEN DHARMASRAYA (Tahun 2003 â 2010) - SURYA, ALBER - (Pendidikan Sejarah, 2014)
Labour economics Social life Digger Sand River District Tassel Year 2003-2010,. The socio-economic history, this thesis aims to determine the socio-economic life of the workers digging the sand between the years 2003 - 2010 in river district Rumbai Dharmasraya. This thesis uses historical research method consists of four stages heuristic (the collection of source material), criticism which is the source of data selectors stage, Interpretation is a stage that has analyzed the sources and historiography that writers get the writing stage. The results of the study, many people residing in riparian areas in the River District Tassel choose to be workers sand diggers. This is because the sand diggers workers work more practical than other jobs and other jobs are also hard to find. Regarding the daily lives of workers digging the sand, their needs increase during 2003-2010 due to the large demand for sand at the time. when it was in the year 2003 are high demand from consumers at the most to 10 trucks. But thats when the depletion of sand in river Tassel and cause damage to the natural beauty.